Compensation and Reward System of Employees in a Business Organization a focus on TOTAL Nigerian Plc - Peace Oluwatoyin Irefin (MultiTech Publisher, 2023)
The objective of the study is to find out how much impact the reward system of TOTAL Plc Asaba has on its employees. The theories assumes expectancy theory according to Victor Vroom and Remuneration method with a sample size drawn from a population of 200 obtained from 2006 National census figures. The sample size was determined using Yaro Yameni’s random sampling technique. The questionnaire was the major instrument used to obtain data. All the hypothesis tested received statistical significance findings for His research indicated that a significant relationship exist between fair reward system and improved employee performance in Nigeria Asaba Plc. The study recommends a develop reward policies and practices that support the achievement of business goals.